2002
DOI: 10.1046/j.1537-2995.2002.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasovagal reactions in apheresis donors

Abstract: The VVR incidence rate was particularly high in women apheresis donors over 45 years old and increased with repeating cycles of apheresis. Smaller CBV, high sensitivity of low-pressure baroreceptors, and citrate effects on cardiovascular reflex might be major factors involved in the high incidence of VVRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
5
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 13 publications
5
51
5
1
Order By: Relevance
“…Most of the vascular injuries were committed by the relatively inexperienced newly joined staff nurses or the technical staffs in the apheresis lab. Female apheresis donors suffering a higher incidence rate of adverse events in comparison to the male apheresis donors have been reported by Tomita et al [7]. However, present study did not report incidence of any adverse events in all 18 female donors who underwent plateletpheresis procedures which may be a chance occurrence only.…”
Section: Discussioncontrasting
confidence: 59%
“…Most of the vascular injuries were committed by the relatively inexperienced newly joined staff nurses or the technical staffs in the apheresis lab. Female apheresis donors suffering a higher incidence rate of adverse events in comparison to the male apheresis donors have been reported by Tomita et al [7]. However, present study did not report incidence of any adverse events in all 18 female donors who underwent plateletpheresis procedures which may be a chance occurrence only.…”
Section: Discussioncontrasting
confidence: 59%
“…Overall, evidence in the literature suggests that the frequency of reactions to apheresis donation is less than that seen in whole blood donation. 7,8 The adverse events during the process of plateletpheresis have been broadly divided into: 5,6,8 • Venipuncture related • Syncope/sweating/faintness • Citrate reactions Pain at the site of venipuncture was noted to be more common because the same vein in one arm is used for inflow and return, resulting in trauma and hematoma to the vein. Citrate is used as primary anticoagulant in donor apheresis procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Tomita et al noted that hypocalcemia may be involved in the onset of vasovagal reactions in apheresis donors. 6 Hypovolemia and vasovagal reactions are treated similarly. The procedure should be temporarily paused and fluid infusion should be started.…”
Section: Resultsmentioning
confidence: 99%
“…Some reports did not assess donors under 17 years of age, because they primarily analyzed allogeneic donors [2,4,6,7]. Previous studies demonstrated the safety of autologous blood donation for pediatric cardiac surgery (n = 80) [13] and homologous donation from high school students [17], and the risk of VVR was reported to be higher in younger autologous or homologous blood donors [2,3,11,15]. Our data revealed that the patients most susceptible to developing VVR were 10-13 years old, followed by those aged 14-17 years.…”
Section: Discussionmentioning
confidence: 99%